Yearbook of the European Convention on Human Rights / Annuaire de la Convention Europeenne des Droits de l’Homme - Council of Europe Staff. author. aut Link
XVII, 704 p. 1 illus.
Keywords: PREMIERE PARTIE TEXTES FONDAMENTAUX ET INFORMATIONS DE CARACTERE GENERAL CHAPITRE I. TEXTES FONDAMENTAUX A. RATIFICATIO~S 3 B. RESERVES ET DECLARATIONS2 3 France 3 Suisse 7 C. DECLARATIONS D' ACCEPTATION DE LA COMPETENCE DE LA COMMIS SION EUROPEENNE DES DROITS DE L'HOMME E~ MATIERE DE RE- QUETES INDIVIDUELLES (Article 25 de la Convention) II Pays-Bas II Suisse II Royaume-Uni 13 D. DECLARATIONS D'ACCEPTATION DE LA JURIDICTION OBLIGATO IRE DE LA COUR EUROPEENNE DES DROITS DE L'HOMME (Article 46 de la Convention) 17 France 17 Islande 19 Pays-Bas 19 Suisse 19 Royaume-Uni 21 E. DEROGATIONS (Article 15 de la Convention) 25 Turquie 25 F. AMENDEME~TS AU REGLEMENT DE LA COUR EUROPEENNE DES DROITS DE L'HOMME 31 G. AMENDEMENTS AU REGLEMENT INTERIEUR DE LA COMMISSION EUROPEENNE DES DROITS DE L'HOMME 35 ANNEXES - Etat des ratifications, declarations et reserves au 31 decembre 1974 74 - Etat des depots des ratifications au 31 decembre 1974 76 VIII TABLE OF CONTENTS CHAPTER II. THE EUROPEAN COMMISSION OF HUMAN RIGHTS A. COMPOSITION B. BIOGRAPHICAL NOTES C. PROCEEDINGS D. SECRETARIAT CHAPTER III. THE EUROPEAN COURT OF HUMAN RIGHTS A. COMPOSITION 94 B. BIOGRAPHICAL NOTES 94 C. SESSIONS AND HEARINGS 8 9 D. REGISTRY OF THE COURT 8 9 CHAPTER IV. PRINCIPAL DEVELOPMENTS IN THE COUNCIL OF EUROPE CONCERNING THE PROTECTION OF HUMAN RIGHTS A. CHRONOLOGICAL LIST OF EVENTS 102 B. WORK OF THE COUNCIL OF EUROPE IN THE FIELD OF HUMAN RIGHTS 106 I. Consultative Assembly 106 2.